THE EFFECTIVENESS OF USING DISCUSSION TASK IN TEACHING SPEAKING OF ANALYTICAL EXPOSITION TEXT - Rini, Indra Waspada; Arifin, Zainal; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractGenerally in teaching and learning process, the students will mostly get the information from the teacher. They are not given much opportunity to share their thoughts especially which enables them to tell the information orally. The purpose of this research was to find out whether discussion task in teaching speaking of analytical exposition text is effective or not to the eleventh grade students of SMA Negeri 3 Pontianak in academic year 2014/2015. It was also designed to find out how significant the effectiveness of using discussion task in teaching speaking of analytical exposition text. The sample of this research was 21 students of XI MIA 2. This research was conducted through pre-experimental research. Data analysis showed that discussion task is effective to be used in teaching speaking of analytical exposition text. The result showed that the t-test result (17.98) was higher than the t-table ? with degree of freedom of 20 (2.086). The effect size result also showed a moderate effect (0.84) based on Cohen?s classification (0.51-ES-1.00). In conclusion, the use of discussion task is moderately effective in teaching speaking of analytical exposition text to the eleventh grade students of SMA Negeri 3 Pontianak in academic year 2014/2015. Keywords: Discussion Task, Analytical Exposition Text, Speaking